Production of Mg thin flakes with enhanced hydrogen storage performance (2024)
ABSTRACT: Flake-like particles are interesting materials for the preparation of alloys and homogeneous nanocomposites, they also have potential use as hydrogen storage materials. However, limited information is available regarding the synthesis of pure magnesium with flake-like morphology. In this study, the successful production of Mg flakes was conducted using a cost-effective and simple method, such as high energy ball milling. Various milling parameters, including different milling times and process control agents, were tested. Optimal conditions led to the formation of coarse flakes with ~1.72 μm thickness, while a two-step milling process produced thinner flakes with submicron thickness (~242 nm). Ductilization of the material and a significant reduction in crystal size during the milling process were observed via X-ray diffraction. Isothermal kinetic tests at 350 ◦C and 20 bar revealed improved hydrogen storage performance for both coarse and thin flakes compared to pristine Mg. Coarse flakes achieved capacities of 4.1 wt% in 60 min while thin flakes reached 4.6 wt% in 6 min, compared to 3.4 wt% achieved in 100 min by pristine Mg. The improved behavior of thin flake-shaped Mg was maintained at 300 ◦C and 20 bar, with 4.5 wt% of hydrogen absorbed in 6 min. Even at lower testing pressures (10 bar) higher capacities were achieved at the expense of slower kinetics. These findings suggest that thin flake-shaped Mg is a suitable material with enhanced performance for hydrogen storage applications.